Safety and efficacy of dual versus triple antithrombotic therapy (DAT vs TAT) in patients with atrial fibrillation following a PCI: a systematic review and network meta-analysis - Abdulaali R Almutairi; Renad M Altoukhi; Reema A Alshouimi; Shahad M Al Rammah; Mohammed Y Alzahrani; Abdulmajeed M Alshehri; Osamah M Alfayez; Majed S Al Yami; Omar A Almohammed (BMJ Open)
Objective Creating an appropriate antithrombotic therapy for patients with atrial fibrillation (AF) who have undergone percutaneous coronary intervention (PCI) remains a dilemma. Several clinical trials compared the use of a dual antithrombotic therapy (DAT) regimen with a direct oral anticoagulants including (apixaban, dabigatran, edoxaban or rivaroxaban) and a P2Y12 inhibitor versus a triple antithrombotic therapy (TAT) that includes a vitamin K antagonist plus aspirin and a P2Y12 inhibitor in patients with AF who have undergone PCI. However, there are no head-to-head trials comparing the DAT regimens to each other. We aimed to compare the efficacy and safety of DAT regimens using a network meta-analysis (NMA) approach.Design A systematic review and NMA of randomised clinical trials.Methods We conducted a systematic literature review to identify relevant randomised clinical trials and performed a Bayesian NMA for International Society on Thrombosis and Haemostasis (ISTH) major or clinically relevant non-major (CRNM) bleeding, all-cause mortality, stroke, myocardial infarction (MI) and stent thrombosis outcomes. We used NetMetaXL V.1.6.1 and WinBUGS V.1.4.3 for the NMA and estimated the probability of ranking the treatments based on the surface under the cumulative ranking curve.Results The comparison between DAT regimens showed no significant difference in the safety or efficacy outcomes. Apixaban regimen was ranked first as the preferred therapy in terms of ISTH major or CRNM bleeding and stroke, with a probability of 52% and 54%, respectively. Rivaroxaban regimen was the preferred therapy in terms of MI and stent thrombosis, with a probability of 34% and 27%, respectively. Dabigatran regimen was ranked first in terms of all-cause mortality, with a probability of 28%.Conclusion The DAT regimens are as safe and effective as TAT regimens. However, ranking probabilities for the best option in the selected outcomes can be used to guide the selection among these agents based on different patients’ conditions.